"But Still It Moves": Screens, Print, and Reading - Baron, Naomi S. (AoIR Selected Papers of Internet Research, 2013)
As the amount of reading people are doing on digital devices mushrooms, a growing number of voices are suggesting that onscreen reading will replace printed hard copy. Digital reading has multiple advantages, including portability, democratic access, and (generally) price. However, concerned scholars are questioning whether reading on digital devices undermines important aspects of reading, including uninterrupted concentration. This paper compares the cases for reading onscreen versus reading in hard copy, considering such variables as cognitive performance, eye-movement, and reader preference. After summarizing studies the author has previously done on college students’ self-reported reading patterns, the paper outlines a study (to be conducted in Spring 2013) that will observe subjects actually reading on a computer screen versus in hard copy. The study will compare the extent to which readers are distracted from the reading tasks (e.g., checking their mobile phones) during the two reading conditions.